Acculturation and Ethnic Hybridism in Immigrant Entrepreneurship - Alessandro Arrighetti; Daniela Bolzani; Andrea Lasagni (Argomenti, 2017)
Received literature on immigrant entrepreneurship describes ethnic firms as founded to meet the needs of an ethnic community, display and use particular configurations of human and social capital drawing on ethnic resources. This is due, according to some authors, to the “acculturation lag” that characterize these entrepreneurs retaining traditional values from the heritage culture. Recent research has however shown that immigrant firms are undergoing significant changes in their organizational structures, such as the incorporation of native or non-co-ethnic partners or employees (i.e., firm multicultural hybridism). Nevertheless, research to date has not investigated whether these changes are accompanied by different acculturation patterns in entrepreneurs operating in companies characterized by different levels of multicultural hybridism. We tackle this question using a unique set of data collected with face-to-face interviews with 130 immigrant entrepreneurs in Northern Italy. Taking a cross-cultural psychological perspective, this study sheds some new light on the acculturation patterns of these different companies and suggests avenues for future research.
Keywords: L26; F22; Z1; 330; Immigrant entrepreneurship; Acculturation; Ethnic hybridism; Multicultural hybridism